One-stage laparoscopic surgery for inspissated bile syndrome: case report and review of surgical techniques - Berger, Steffen (Springer International Publishing, 2013)
Inspissated bile syndrome in a 6 week old boy was unresponsive to oral ursodesoxycholic acid. Intraoperative cholangiography revealed complete obstruction of the common bile duct. Therefore, the gallbladder fundus was pulled out through a laparoscopy port site and sutured to the fascia. A catheter was positioned into the infundibulum for irrigation with ursodesoxycholic acid. At day 8 complete resolution of the plug and free passage of contrast medium into the duodenum was documented radiologically. The catheter was removed, skin closed spontaneously without a second surgery for closure of the gall bladder.